P121 The study of the hypercoagulable state in Crohn disease: Results of a prospective comparative study. (27th May 2021) - Serghini, M; Ben Youssef, H; Laabidi, A; Ben Mustapha, N; Hafi, M; Fekih, M; Boubaker, J
Abstract: Background: The risk of thrombosis is increased in Crohn disease (CD). Abnormalities in hemostasis during CD have been evaluated in several studies but the results remain controversial. The thrombin generation assay (TGA) provides an overall assessment of hemostasis compared to traditional tests. The purpose of this work was to study the hypercoagulable state in patients with CD through TGA and to correlate it with the clinical and biological status of the disease. Methods: This was a prospective comparative study, collating 50 patients diagnosed with CD and compared to 50 matched controls according with age and sex, between May 2016 and January 2020. TGA was effectuated in both groups. Data related to CD were collected. Parameters of lag time (min), time to peak (min), peak (nM), endogenous thrombin potential (ETP in nM.min) and velocity index (VI in nM/min) were analyzed. Laboratory parameters of inflammation, factor VIII and anti-coagulant factors were evaluated in patients. Results: Median age of patients was 44.02 years (29 men and 21 women). The proportion of patients in remission was 66%. The mean levels of FVIII (285.1±175.2 vs 133.8±41.9; p=0.001), ProteinC (117±22.8 vs 103.2±13.6; p=0.003) and Antithrombin (97.1±16.9 vs 80.65±13.2; p=0.001) were significantly higher in patients with CD compared to controls. No significant difference was found for the rates of ProteinS. Thrombin generation was faster in patients with CD compared to controls (IV: 163.9±41.9 vs 138.2±67.4; p=0.04) and in cases of fistulizing or stenosing phenotype compared to the inflammatory phenotype. Thrombin generation was higher in patients: hospitalized compared to those seen as outpatients (ETP: 1515±406.6 vs 1248.2 + 380.8; p=0.05), treated with corticosteroids (ETP=1718.7 + 126.9) compared to the rest of the patients (p=0.03), with CRP> 6 mg/L compared to those with normal CRP (ETP= 1515 + 384.8 vs 1245 + 348.2) (p=0.02) and with hyperfibrinogenemia level compared to those with normal fibrinogen (Peak = 351.6±74.1 vs 294.9 ±64.4) (p= 0.03). A significant positive correlation was noted between the parameters of TGT, CRP and fibrinogen. ETP value was significantly correlated with CRP (r=0.45; p=0.001) and fibrinogen (r=0.35; p=0.02). This allowed us to determine two biological scores correlating ETP and CRP (ETP=1384 + 2.9 x CRP), as well as fibrinogen level (ETP=1060.7 + 130.5 x Fibrinogen) Conclusion: Thrombin generation appears to be more accelerated in patients with CD than in controls. This hypercoagulability is associated with hospitalization, stenosing and fistulizing phenotypes, elevated CRP and fibrinogen and corticosteroid therapy. The determination of ETP from CRP and fibrinogen would be a valuable tool for assessing the state of coagulability in these patients.